5-(4-Methylphenyl)-3-phenylcyclohex-2-en-1-one - Shaaban K. Mohamed; Mehmet Akkurt; Antar A Abdelhamid; Kuldip Singh; Omyma A. A. Abd Allah (Acta Crystallographica Section E, 2012)
In the title compound, C19H18O, the cyclohexene ring has an envelope conformation with the methine C atom on the flap. The phenyl and methylphenyl rings form a dihedral angle of 85.93 (11)°. The crystal packing is consolidated by van der Waals forces and weak C—H...π interactions.